Efficient Human Genome Editing Using SaCas9 Ribonucleoprotein Complexes. Issue 7 (17th May 2019) - Wang, Yufei; Wang, Bang; Xie, Haihua; Ren, Qianwen; Liu, Xiexie; Li, Fanfan; Lv, Xiujuan; He, Xiubin; Cheng, Congsheng; Deng, Ruzhi; Li, Jin; Zhao, Junzhao; et al.
Abstract : Genome editing using RNA‐guided nucleases in their ribonucleoprotein (RNP) form represents a promising strategy for gene modification and therapy because they are free of exogenous DNA integration and have reduced toxicity in vivo and ex vivo. However, genome editing by Cas9 nuclease from Staphylococcus aureus (SaCas9) has not been reported in its RNP form, which recognizes a longer protospacer adjacent motif (PAM), 5′‐NNGRRT‐3′, compared with Streptococcus pyogenes Cas9 (SpCas9) of 5′‐NGG‐3′ PAM. Here, SaCas9‐RNP‐mediated genome editing is reported in human cells. The SaCas9‐RNP displayed efficient genome editing activities of enhanced green fluorescent protein (EGFP) coding gene as well as three endogenous genes ( OPA1, RS1, and VEGFA ). Further, SaCas9‐RNP is successfully implemented to correct a pathogenic RS1 mutation for X‐linked juvenile retinoschisis. It is also shown that off‐target effects triggered by SaCas9‐RNP are undetectable by targeted deep sequencing. Collectively, this study demonstrates the potential of SaCas9‐RNP‐mediated genome editing in human cells, which could facilitate genome‐editing‐based therapy. Abstract : Ribonucleoprotein (RNP) form of RNA‐guided nuclease is free of exogenous DNA and quickly degrades within target cells that represent a promising approach for the manipulation of the genome. In this study, the authors establish a robust genome‐editing pipeline of Staphylococcus aureus Cas9 (SaCas9)‐RNP, a smaller RNA‐guided nuclease with more restricted protospacer adjacent motif (PAM) (5′‐NNGRRT‐3′) than Streptococcus pyogenes Cas9 (SpCas9) (PAM:5′‐NGG‐3′), providing proof‐of‐concept editing on human‐diseases‐causative genes, demonstrating the potential of SaCas9‐RNP for human gene therapy.